An Imidazoline Derivative Functionalized Cotton Fabric for Pesticide Protective Clothing - Abirami, R.; Selvakumar, N. (Asian Journal of Chemistry, 2013)
Protective cotton clothing at the time of spraying of the pesticides in the agricultural field for the application is very much essential. In the present work, a simple approach was applied to make the cotton fabric with enhanced pesticide protection. A twill fabric and the same fabric subjected to raising operation were functionalized with 1,3-dimethylol-4,5-dihydroxy-2-imidazolidone followed by chlorination with sodium hypochlorite to detoxify the pesticide on its absorption in the fabric. The study was carried out in a newly defined test equipment and using pesticides borne air. An organophosphate pesticide, dimethoate was used for testing. Analysis indicated detoxification of pesticide and the extent of detoxification depended on the chlorine content in the fabric. There was also reduced penetration of pesticide through the fabric. Raised fabrics gave better performance than the unraised fabric. Wet conditions were verified to enhance detoxification.